Pengaruh Belanja Modal Terhadap Indeks Pembangunan Manusia Kota Palembang - Anton Trianto; Aras Tulip; Muhammad Deni (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2017)
Human development is an important part of a series ofprocesses undertaken by a country or region to change for the better future. Human Development Index (HDI) becomesone of the benchmarks in assessing the success of human development. To support human development government must allocate an effective public budget. This study aims to see how the effect of capital expenditure on increasing HDI in Palembang City. The data used is the primary data for the period of 2013-2016. The analysis technique is simple regression analysis of two variables, namely HDI as dependent variable and capital expenditure (lag 1) as independent variable. The result shows that capital expenditure has a significant influence on the increase of HDI.